Carbon starvation reduces carbohydrate and anthocyanin accumulation in red‐fleshed fruit via trehalose 6‐phosphate and MYB27. (30th December 2019) - Nardozza, Simona; Boldingh, Helen L.; Kashuba, M. Peggy; Feil, Regina; Jones, Dan; Thrimawithana, Amali H.; Ireland, Hilary S.; Philippe, Marine; Wohlers, Mark W.; McGhie, Tony K.; Montefiori, Mirco; Lunn, John E.; et al.
Abstract: Kiwifruit ( Actinidia spp.) is a recently domesticated fruit crop with several novel‐coloured cultivars being developed. Achieving uniform fruit flesh pigmentation in red genotypes is challenging. To investigate the cause of colour variation between fruits, we focused on a red‐fleshed Actinidia chinensis var. chinensis genotype. It was hypothesized that carbohydrate supply could be responsible for this variation. Early in fruit development, we imposed high or low (carbon starvation) carbohydrate supplies treatments; carbohydrate import or redistribution was controlled by applying a girdle at the shoot base. Carbon starvation affected fruit development as well as anthocyanin and carbohydrate metabolite concentrations, including the signalling molecule trehalose 6‐phosphate. RNA‐Seq analysis showed down‐regulation of both gene‐encoding enzymes in the anthocyanin and carbohydrate biosynthetic pathways. The catalytic trehalose 6‐phosphate synthase gene TPS1.1a was down‐regulated, whereas putative regulatory TPS7 and TPS11 were strongly up‐regulated. Unexpectedly, under carbon starvation MYB10, the anthocyanin pathway regulatory activator was slightly up‐regulated, whereas MYB27 was also up‐regulated and acts as a repressor. To link these two metabolic pathways, we propose a model where trehalose 6‐phosphate and the active repressor MYB27 are involved in sensing the carbon starvation status. This signals the plant to save resources and reduce the production of anthocyanin in fruits. Abstract : In carbon‐starved red‐fleshed kiwifruit, both carbohydrate and anthocyanin concentrations were greatly reduced. Our model suggests that anthocyanin biosynthesis was actively repressed by MYB27 via trehalose 6‐phosphate signalling to conserve carbon.